Do institutional investors get affected by biases in theirindividual investments - KOÇ, İDİL ÖZLEM (My University, 2022)
This study focuses on the individual investments of employees of Turkish finance sector in capital markets. The study has two main objectives. One of these is to investigate whether or not institutional investors show “rational investor behaviors” also in relation to their individual investments. For this reason, it is aimed to reveal whether or not the institutional investor deviates from their mindset employed while they are doing their job professionally and is affected by biases when their own individual investments are in question. Another purpose of the study is to find the bias or biases among representativeness, conservatism and overconfidence biases by which Turkish institutional investors are influenced in their individual investments. For this purpose, institutional investors in Istanbul (Turkey) who could be reached by using the method of convenience sampling were directed questions on their representativeness, conservatism and overconfidence biases in their individual investment decisions, 2 hypotheses were formed for each type of bias, and these hypotheses were tested using Pearson chi-squared test. As a result of the analyses, it was observed that Turkish institutional investors were not influenced by overconfidence bias in their individual investments. On the other hand, institutional investors were found to be affected by conservatism bias. Additionally, no precise conclusion could be made regarding whether or not representativeness bias was effective on the decisions of the institutional investors about their individual investments. In the study, in general, it was concluded that the institutional investors were influenced by behavioral biases by showing normal investor behaviors under certain conditions regarding their decisions on their individual investments, rather than showing rational investor behaviors.
Keywords: Institutional investor; rational-irrational investor; representativeness bias; conservatism bias; overconfidence bias